The cost of accessing infant HIV medications and health services in Uganda - Bergmann, Julie N.; Wanyenze, Rhoda K.; Stockman, Jamila K. (AIDS Care, 2017)
Patient costs are a critical barrier to the elimination of mother to child HIV transmission. Despite the Ugandan government providing free public HIV services, infant antiretroviral (ARV) prophylaxis coverage remains low (25%). To understand costs mothers incur in accessing ARV prophylaxis for their infants, we conducted a mixed methods study to quantify and identify their direct costs. We used cross-sectional survey data and focus group discussions from 49 HIV-positive mothers in Uganda. Means and standard deviations were calculated for the direct costs (e.g., transportation, caretaker, services/medications) involved in accessing infant HIV services. The direct cost of attending HIV clinic visits averaged $3.71 (SD = $3.52). Focus group discussions identified two costs hindering access to infant HIV services: transportation costs and informal service charges. All participants reported significant costs associated with accessing infant HIV services – the equivalent of 2–3 days’ income. To address transportation costs, community and home care models should be explored. Additionally, stricter policies and oversight should be implemented to prevent informal HIV service charges.
Keywords: Patient costs; direct costs; HIV-exposed infants; mother to child transmission of HIV; Sub-Saharan Africa